Analysis of the Usability Level of the JKN Mobile Application Using the User Experience Questionnaire (UEQ) and Importance–Performance Analysis (IPA) Methods - Haris, Gendhi; Tri Julianto, Indri; Ridwan Ibrahim, Maulana (Deparment Information System, Siliwangi University, 2025)
The JKN Mobile application developed by BPJS Kesehatan is a digital service for National Health Insurance (JKN) participants to access features for checking membership, online queues, and complaint services. JKN Mobile contributes significantly to the digitalization of healthcare services, but various negative reviews still emerge, especially regarding the interface aspect. This study analyzes the usability level of the application using the User Experience Questionnaire (UEQ) and Importance Performance Analysis (IPA) methods. The UEQ assesses six aspects of user experience, while IPA maps attributes based on importance and performance. The analysis results show a gap between expectations and experience. Clarity (1.1056, 0.4021), efficiency (1.0181, 0.0026), and appeal (1.0946, -0.019) fall into the